"She's Built Like a Tank": Player Reaction to Abby Anderson in The Last of Us: Part II. Issue 5 (July 2023) - Tomkinson, Sian
The depiction of female characters in video games is highly contentious. The pushes for increased diversity following Gamergate have heralded more varied representations of women in both independent and Triple A games. One particularly interesting video game in this context is Naughty Dog's 2020 action-adventure title The Last of Us: Part II . The game received extremely divisive criticism in part due to Abby Anderson and her functions in the game. Many players were outraged at her muscular, "masculine" build, considering it inaccurate for a woman living in a post-apocalyptic setting, and a form of virtue-signalling. In this paper I examine these players' complaints regarding Abby and consider how they fit within gaming discourses of realism, immersion, and escapism. I explore what elements players consider to be acceptable as 'realism' in the context of a post-apocalyptic action-horror video game, considering a prevalent discourse that video games are being increasingly politicised.